Atypical TDP‐43 protein expression in an ALS pedigree carrying a p.Y374X truncation mutation in TARDBP. (24th July 2022) - Cooper‐Knock, Johnathan; Julian, Thomas H.; Feneberg, Emily; Highley, J. Robin; Sidra, Maurice; Turner, Martin R.; Talbot, Kevin; Ansorge, Olaf; Allen, Scott P.; Moll, Tobias; Shelkovnikova, Tatyana; Castelli, Lydia; et al.
Abstract: We describe an autosomal dominant, multi‐generational, amyotrophic lateral sclerosis (ALS) pedigree in which disease co‐segregates with a heterozygous p.Y374X nonsense mutation within TDP‐43. Mislocalization of TDP‐43 and formation of insoluble TDP‐43‐positive neuronal cytoplasmic inclusions is the hallmark pathology in >95% of ALS patients. Neuropathological examination of the single case for which CNS tissue was available indicated typical TDP‐43 pathology within lower motor neurons, but classical TDP‐43‐positive inclusions were absent from motor cortex. The mutated allele is transcribed and translated in patient fibroblasts and motor cortex tissue, but overall TDP‐43 protein expression is reduced compared to wild‐type controls. Despite absence of TDP‐43‐positive inclusions we confirmed deficient TDP‐43 splicing function within motor cortex tissue. Furthermore, urea fractionation and mass spectrometry of motor cortex tissue carrying the mutation revealed atypical TDP‐43 protein species but not typical C‐terminal fragments. We conclude that the p.Y374X mutation underpins a monogenic, fully penetrant form of ALS. Reduced expression of TDP‐43 combined with atypical TDP‐43 protein species and absent C‐terminal fragments extends the molecular phenotypes associated with TDP‐43 mutations and with ALS more broadly. Future work will need to include the findings from this pedigree in dissecting the mechanisms of TDP‐43‐mediated toxicity. Abstract : In this study Cooper‐Knock et al identified an autosomal dominant ALS pedigree associated with p.Y374X‐TARDBP. In patient tissue the authors confirmed reduced TDP‐43 protein expression, abnormal TDP‐43 fragmentation and deficient TDP‐43‐mediated splicing. This work extends the phenotypes associated with TDP‐43 mutations.